Effectiveness of planned teaching program on home management and its side effects in terms of knowledge among caregivers of patients receiving chemotherapy at selected tertiary care hospital, Belagavi - Jonathan Borges; Preeti Bhupali; Deepak Bagi (Indian Journal of Health Sciences and Biomedical Research KLEU, 2018)
INTRODUCTION: Cancer is most fatal disease, and the caregivers taking care of the cancer patients have a vital role to play in their health-care wellness. As chemotherapy is one of the treatments for cancer, the side effects of chemotherapy are very important to be manage at home by the caregivers. The most effective way of giving information to the caregivers was by giving a planned teaching programme (PTP) and enhancing their knowledge regarding home management and its side effects of chemotherapy. OBJECTIVES: The objective of this study was to assess the knowledge of caregivers of patients receiving chemotherapy; to administer PTP on home management and its side effects in terms of knowledge among caregivers of patients receiving chemotherapy; and to evaluate the effectiveness of PTP on home management and its side effects in terms of knowledge among caregivers of patients receiving chemotherapy. MATERIALS AND METHODS: A preexperimental research was conducted on sixty caregivers of patients receiving chemotherapy. The study was conducted at KLE'S Belgaum Cancer Hospital, Belagavi, using one group pretest and posttest design. The demographic variables analyzed for the study were age, gender, religion, education, and income. The study was conducted using purposive sampling technique on a sample of 60 caregivers by knowledge-structured questionnaire to collect the data regarding home management and its side effects in terms of knowledge among caregivers of patients receiving chemotherapy. RESULTS: The pre- and post-test frequency and percentage of knowledge scores of respondents regarding home management and its side effects in terms of knowledge among caregivers of patients receiving chemotherapy revealed that pretest (13.34%) subjects had poor knowledge, 75% had average knowledge, and 11.66% had good knowledge scores, where posttest (6.67%) subjects had poor knowledge, 65% had average knowledge, and 28.33% had good knowledge scores. The effectiveness of PTP was assessed with paired t-test and it was revealed that there was a significant gain in knowledge at 0.05 level of significance. CONCLUSION: The study concluded that PTP was as effective teaching strategy to improve the knowledge regarding home management and its side effects in terms of knowledge among caregivers of patients receiving chemotherapy.